Enhancing the accountability of Malaysian government linked companies through sustainable competitive advantage and value creation / Nur Nadiah Zulkarnain ...[et al.] - Zulkarnain, Nur Nadiah; Nik Abdullah, Nik Herda; Said, Jamaliah; Rosli, Mohamad Hafiz (Universiti Teknologi MARA Cawangan Selangor, 2015)
Value creation is an essential element needed in every organization for sustainability in the global market. Value creation can be reflected through continuous improvement in the organization's earnings per share and the high level of operational effectiveness and competitiveness. Government linked companies (GLCs) are organizations in which the government contributes more than fifty percent of capital and is expected to be actively involved in value creation to reflect high level accountability to taxpayers' money. However, despite many efforts by the government to improve the performance of GLCs, several studies have found a lack of value creation among GLCs that led to their closure. The resource-based view argues that an organization that possesses capabilities often create more value. This study aims to test resource-based view's proposition by examining whether companies with high sustainable competitive advantage can create high value. This study examines four components of sustainable competitive advantage: innovation, entrepreneurship, learning, and market orientation. Results show that the existence of the significant relationship among learning orientation, entrepreneurship orientation, and market orientation on value creation. However, this study finds that high innovation does not lead to better value creation in the context of Malaysian GLCs.